Alcohol is a metabolic bully. - Clements, Jeremy (My University, 2007)
The purpose of this project was to review the literature on the metabolic effects of alcohol and synthesize the information into a message that is applicable to college students.
Color poster with text summarizing information obtained from a literature review by Jeremy Clements, advised by Don Bredle.
Keywords: Alcohol in the body.; Alcohol--Metabolism.; Alcohol--Nutritional aspects.; Alcohol--Physiological effect.; Posters.